2017
DOI: 10.1590/0001-3765201720160452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate on the richness and composition of Neotropical cave fauna

Abstract: The food base in the subterranean environment consists mainly of allochthonous materials. In this environment the resources are distributed generally in a heterogeneous dispersed way and the distribution of resources and their availability determine where the terrestrial invertebrates will reside, which is important for understanding ecological relationships and to establish conservation strategies. Thus, we tested how the complexity of substrates influences the richness and composition of the subterranean ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In this study, we showed that stepping activity from tourism affects the distribution of bat guano in the touristic part of the cave and that bat guano was an important driver for nontroglobitic species composition. Furthermore, both troglobitic and non-troglobitic species composition were influenced by the presence of water puddles and fine sediment, both consisting of suitable microhabitats according to the literature (Ferreira and Souza-Silva 2001;Zepon and Bichuette 2017). Therefore, in order to combine the activities of tourism with the preservation of these hypogean environments, when making a management plan, one should be aware of such cave micro-habitats, since those are more prone to shelter the cave invertebrate fauna, including some specific, more specialised invertebrate species (Ferreira and Martins 1998;Ferreira et al, 2007;Pellegrini and Lopes Ferreira 2012;Sánchez-Fernandez et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we showed that stepping activity from tourism affects the distribution of bat guano in the touristic part of the cave and that bat guano was an important driver for nontroglobitic species composition. Furthermore, both troglobitic and non-troglobitic species composition were influenced by the presence of water puddles and fine sediment, both consisting of suitable microhabitats according to the literature (Ferreira and Souza-Silva 2001;Zepon and Bichuette 2017). Therefore, in order to combine the activities of tourism with the preservation of these hypogean environments, when making a management plan, one should be aware of such cave micro-habitats, since those are more prone to shelter the cave invertebrate fauna, including some specific, more specialised invertebrate species (Ferreira and Martins 1998;Ferreira et al, 2007;Pellegrini and Lopes Ferreira 2012;Sánchez-Fernandez et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Electrogenic species, therefore, appear to be well-suited for life in caves in which there are no visual signals. However, electrogenesis is energetically costly; caves commonly have reduced food resources (Zepon and Bichuette, 2017;Pipan et al, 2018). As a first step in describing changes and adaptations for cave life in electrogenic fishes, we compared the electric behavior and locomotor movement of a population of troglobitic weakly electric fish Eigenmannia vicentespelea to a nearby population of epigean fish, Eigenmannia trilineata.…”
Section: Discussionmentioning
confidence: 99%
“…The municipality of Presidente Olégário is characterized by human occupation, with natural landscapes almost completely suppressed and replaced by pastures and large areas of extensive agriculture (Secutti and Bichuette 2013). Additionally, gas extraction and hydroelectric projects are being implemented (Secutti and Bichuette 2013;Zepon and Bichuette 2017). Several of these directly impact the caves and their surroundings (Zepon and Bichuette 2017) (Table 1; Fig.…”
Section: Methodsmentioning
confidence: 99%